Análise das manifestações patológicas estruturais em ponte de concreto armado sobre o rio ceará-mirim, extremoz-RN - Silva, Iury Soares da (2022)
This work presents a case study carried out on the bridge over the Ceará-Mirim river in the municipality of Extremos/RN and aims to present the pathological manifestations found, calculate the degree of deterioration of the structure (Gd) and expose solutions adopted for the recovery of pathological anomalies. The methodology proposed by Lichtenstein (1976) was adopted consisting briefly of three stages: (1) site inspection to identify the nature and origin of pathological manifestations; (2) the diagnosis of the anomaly; (3) the solution adopted to solve the problem. The degree of deterioration of the structure was calculated according to the methodology proposed by Klein et al (1991) in its latest updated version by Fonseca (2007). To develop the methodology, pillars, beams, platform running way were analyzed. As a result, it was found the of the columns (Gdpilar = 207,16), the beams (Gdviga = 173,81) the bridge board (Gdtabuleiro = 10,54) and finally the general deterioration of the structure (Gd) = 139.07), so that the bridge structure was classified in critical situation, with planning for emergency inspection and immediate actions aimed at recovering the bridge structure.